Anti-inflammatory, analgesic, and antipyretic potential of Oxystelma esculentum (L. f.) Sm. using in vitro, in vivo, and in silico studies - Sherif, Asmaa E.; Sajid-ur-Rehman, Muhammad; Asif, Muhammad; Qadeer, Iram; Khan, Kashif ur Rehman (Frontiers in Pharmacology, 2024)
The objective of the current study was to evaluate O. esculentum 's potential as anti-inflammatory, analgesic, and antipyretic by using different animal models. Phytochemical profile was determined by total phenolic contents (TPC) total flavonoid contents (TFC) followed by high-performance liquid chromatography (HPLC) technique. In vitro anti-inflammatory potential of O. esculentum ethanolic extract (OEE) was evaluated by lipoxygenase enzyme inhibition activity and human red blood cell (HRBC) membrane stability assay. In vivo anti-inflammatory potential of the plant was determined by carrageenan-induced paw edema test, analgesic potential by hot-plate, tail flicking , formalin-induced analgesia, acetic acid-induced writhing activities, and yeast-induced elevation of body temperature. The values of total phenolic contents (212.6±3.18 µg GAE/g) and total flavonoid contents (37.6±1.76 µg QE/g) were observed. The antioxidant capacity of OEE showed significant DPPH (2,2-Diphenyl-1-picrylhydrazyl) (266.3±7.35 μmol TE/g), ABTS (2,2′-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) (1066.3±7.53 μmol TE/g) and FRAP (Ferric Reducing Antioxidant Power Assay) (483.6±3.84 μmol TE/g) results. HPLC analysis demonstrated phytocompounds with anti-inflammatory potentials such as chlorogenic acid, gallic acid, 4-hydroxybenzoic acid, caffeic acid, ferulic acid, and coumarin. The plant showed in vitro anti-inflammatory action by the inhibition of lipoxygenase enzyme with a high percentage (56.66%) and HRBC membrane stability (67.29%). In vivo studies, OEE exhibited significant (P<0.05) anti-inflammtory (carrageenan-induced paw edema model), analgesic (hot-plate, tail flicking, formalin-induced analgesia and acetic acid-induced writhing) and antipyretic response (reduce the rectal temperature) at different doses (100, 300, and 500mg/kg). Molecular docking studies showed significant binding affinities of phytocompounds compared to indomethacin and predicted various binding interactions for stable conformations. The results of in vitro, in vivo, and in silico studies supported the anti-inflammatory, analgesic, and antipyretic potential of Oxystelma esculentum.